Frontliner: Does it play a role in reducing the waiting time of outpatient registration? - Hapsari, Riva Redianita; Fitriasari, Nikma; Pratama, Bramantya Surya (Jurnal Kedokteran Brawijaya)
Outpatient services often become the first gateway for patient access to hospital services. One of the minimum service standards for improving the quality of hospital services is collecting the medical record files in less than 10 minutes. This study aimed to prove whether the frontliners can help cut the process in the outpatient registration by revising the SOP and describing the outline of the outpatient service flow involving the frontliners at Ananda Srengat Hospital. The study applied quantitative analysis methods with a descriptive analysis technique to patients, medical records unit employees, outpatients, and related units. A total population of 10 people was taken within one week. The methods of collecting data were using a questionnaire instrument and a stopwatch. The results of this study are the changes in the SOP and the description of frontliner tasks in assisting the process of sorting files that can reduce the process of registration waiting time.